Plans d’eau glaciaires et isostasie dans les bassins de la haute Ware et de la rivière Otter, Massachusetts (2e partie) - Cestre, Gilbert (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1973)
The present study is one of the unpublished research projects which are known to have been conducted in New England and in Eastern Canada under the guidance of the late Richard J. LOUGEE, long-time professor of Geomorphology at Clark University. Over a number of years, this writer has worked in close relationship with Lougee and much evidence in the field was studied together. It is believed that here has been recorded a most detailed work of surveying, and this undoubtedly accounts for the somewhat exceptional results that will be presented.The area selected for this study (about 80% of it is woodland) is located in the highlands of Central Massachusetts in Worcester County, about twenty miles (32 kilo-meters) northwest of the city of Worcester. It consists of the valley of the Otter River draining north, and of a small portion of the East Branch of the Ware River draining south. Since completion of this study, parts of the low area which held the ancient glacial lakes have been flooded to become water reservoirs.That proglacial lakes, though temporary they may have been, once submerged much of the area under study, is shown by an abundance of deltas, kames, eskers and deltaic kames terraces. It is believed that all of these were built under water in such lakes. Other features, such as kettle-holes and glacial outlets, especially ice-marginal channels cutdiagonally down the slope, have also been studied. By plotting on a profile of the most characteristic elevations (often carefully surveyed), it is possible to find the water planes of ancient proglacial lakes. To this must be added experiments conducted in a sedimentation tank as also measurements of both the imbrication of cobbles in eskers and the « smoothness indexes » of such stones and pebbles, using A. Cailleux' methods.Thus were obtained results which tend to show that :1- the area under study probably was in a deep interlobate space created between the Connecticut Valley lobe to the west and the Boston Basin lobe to the east ;2— ice-marginal channels are an indication of the existence of a thick, fast-retreating ice border ;3- an isostatic balance restored itself by sometimes quick and strong adjustments of the crust of the earth ;4— an early upwarping, made up of various zones of tilting articulated on hinge lines, has been referred to as Hubbard Uplift and is the earliest known in the post-Glacial history of New England.